2022
DOI: 10.1021/acs.oprd.2c00180
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Microwave Flow System for Scalable Synthesis of Alkyl Imidazolium-type Ionic Liquids

Abstract: A continuous flow auto-frequency tuning single-mode microwave reactor is disclosed as a powerful platform to synthesize alkyl imidazolium salts as ionic liquids/ionic liquid precursors in up to near-quantitative yields, 100−600 g h −1 productivities and record space-time yields. Challenges faced, including viscosity changes, dielectric property changes, and phase separations, were addressed by different operation modes of the reactor without reactor redesigning. Depending on the purpose, this highly productive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Take the most popular imidazolium-based ILs as an example, the synthesis of these chemicals generally needs over days for refluxing and subsequent purifications. 42 In this case, the manufacture of ILs in conjunction with microwave (MW) chemistry is promising to meet the claims of "green chemistry" due to the potential of MW heating to accelerate chemical synthesis via rapid and direct transfer of energy to MWabsorbing chemicals. The first usage of MW technology in the IL field was reported by Varma and Namboodiri in 2001.…”
Section: Microwave: Unlock New Thoughtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Take the most popular imidazolium-based ILs as an example, the synthesis of these chemicals generally needs over days for refluxing and subsequent purifications. 42 In this case, the manufacture of ILs in conjunction with microwave (MW) chemistry is promising to meet the claims of "green chemistry" due to the potential of MW heating to accelerate chemical synthesis via rapid and direct transfer of energy to MWabsorbing chemicals. The first usage of MW technology in the IL field was reported by Varma and Namboodiri in 2001.…”
Section: Microwave: Unlock New Thoughtsmentioning
confidence: 99%
“…In terms of Question 4, the time-consuming and energy-consuming production of ILs still hinders their practical utility as solvents or electrolytes. Take the most popular imidazolium-based ILs as an example, the synthesis of these chemicals generally needs over days for refluxing and subsequent purifications . In this case, the manufacture of ILs in conjunction with microwave (MW) chemistry is promising to meet the claims of “green chemistry” due to the potential of MW heating to accelerate chemical synthesis via rapid and direct transfer of energy to MW-absorbing chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Domański et al described the acceleration of alkylimidazolium salt synthesis using a continuous flow and auto-frequency tuning microwave reactor platform. 47 The application of microwaves enabled rapid product formation, with residence times under 10 minutes, yields approaching 97%, and production rates (PRs) on the order of several hundreds of grams per hour. Cao et al also demonstrated a MW-assisted water-free flow synthesis of pyridinium salts on a similar timescale with >94% yield.…”
Section: Introductionmentioning
confidence: 99%